2020
DOI: 10.21163/gt_2020.152.13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Industrial Development at the Coast of Lévrier Bay Through the Spatio-Temporal Study of Metallic Contaminants (Cd, Pb, Cu, Zn and Hg) in Surface Sediments

Abstract: Lévrier Bay is located at the northern Atlantic Mauritanian coast, between 19 ° 20'N and 20 ° 40'N and between the coast and 17 ° 20W in the vicinity of Cap Blanc peninsula. This work aims at contributing to the assessment the impact of industrial development in the Lévrier Bay through the study of the toxicity and the spatio-temporal distribution of trace metals (Cd, Pb, Cu, Zn and Hg) in surface sediments, during the four hydrological seasons. The trace metal concentrations of the sediments are generally het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In addition, (Zamel et al, 2010) showed that 75,632 cubic meters of wastewater are discharged into the bay every day, including 3 cubic meters of oily water and 51,755 tons of solid waste, which is a major source of harmful pollution to the bay environment. Cheikh et al (2020) showed that Levrier Bay suffers from untreated wastewater discharges from fishmeal plants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, (Zamel et al, 2010) showed that 75,632 cubic meters of wastewater are discharged into the bay every day, including 3 cubic meters of oily water and 51,755 tons of solid waste, which is a major source of harmful pollution to the bay environment. Cheikh et al (2020) showed that Levrier Bay suffers from untreated wastewater discharges from fishmeal plants.…”
Section: Introductionmentioning
confidence: 99%